2006
DOI: 10.1007/s11906-006-0035-6
|View full text |Cite
|
Sign up to set email alerts
|

Proximal tubular function and salt sensitivity

Abstract: Blood pressure response to changes in dietary salt intake is highly variable among individuals. This heterogeneity results from the combined effects of genetic and environmental determinants. In recent years, considerable progress has been made in our understanding of the pathogenic mechanisms leading to the development of salt-sensitive hypertension. Much information has come from the investigation of rare monogenic forms of salt-sensitive hypertension, which has focused attention on alterations of renal sodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 69 publications
0
32
0
Order By: Relevance
“…We have reported previously that FE Li remains inappropriately low in some hypertensive patients, reflecting an enhanced proximal sodium reabsorption and salt sensitivity. 7 A third possible factor is the smaller decrease in sodium excretion under the LS diet in the hypertensive participants. Although the same dietary regimen was applied to normotensive and hypertensive subjects, the compliance of the latter appears to be less than that of the former.…”
Section: Pruijm Et Al Salt Intake and Renal Oxygenationmentioning
confidence: 99%
See 1 more Smart Citation
“…We have reported previously that FE Li remains inappropriately low in some hypertensive patients, reflecting an enhanced proximal sodium reabsorption and salt sensitivity. 7 A third possible factor is the smaller decrease in sodium excretion under the LS diet in the hypertensive participants. Although the same dietary regimen was applied to normotensive and hypertensive subjects, the compliance of the latter appears to be less than that of the former.…”
Section: Pruijm Et Al Salt Intake and Renal Oxygenationmentioning
confidence: 99%
“…[1][2][3][4] Patients with essential and secondary forms of hypertension are often characterized by increased sodium retention either in the proximal or in the distal nephron segments. [5][6][7] Experimentally, the renal handling of sodium is a process known to have an important impact on renal tissue oxygen consumption. 8 Indeed, the tubular sodium reabsorption requires active transport systems that are energy consuming.…”
mentioning
confidence: 99%
“…Burnier et al, 57 using the endogenous renal lithium clearance (Cl Li ) method, a well-validated measure of total proximal tubular sodium reabsorption, found that SS subjects do not suppress proximal sodium reabsorption as effectively as SR ones in response to sodium loading. Cl Li measurements do not permit distinction between the several mechanisms mediating proximal tubular sodium reabsorption, but the finding is consistent with the renal hemodynamic studies reviewed above: the increase in filtration fraction observed in SS hypertensive subjects should increase peritubular oncotic pressure and promote sodium reabsorption in the proximal tubule.…”
Section: Segmental Renal Tubular Sodium Transportmentioning
confidence: 99%
“…9 In these black subjects, dietary sodium intake was positively associated with systolic blood pressure in subjects with low FE Li but not in those with high FE Li . The mean urinary sodium excretion per day was ≈50 mmol in these black subjects 9 and 163 mmol in our study subjects. The relationship between blood pressure and sodium renal handling might differ from low to high dietary sodium intake.…”
Section: )mentioning
confidence: 77%
“…Among the complex mechanisms, renal sodium handling must play a major role in the determination of this interindividual variability. 9,10 We hypothesize that sodium dietary intake and renal handling interact to influence blood pressure and believe that illustration of this relationship would be clinically relevant for the prevention and management of hypertension by sodium restriction.…”
mentioning
confidence: 99%